THE CONTENT STRATEGY TOOLKIT methods, guidelines, and templates for getting content right - Casey, Meghan (NEW RIDERS, 2023)
In this essential guide, Meghan Casey outlines a step-by-step approach for successful content strategy, from planning and creating your content to delivering and managing it. Armed with this book, you can confidently tackle difficult activities like explaining clearly to your boss or client what's wrong with their content, getting the budget to do content work, and aligning stakeholders on a common vision. Having The Content Strategy Toolkit at your side is like hiring your own personal consulting fi rm. You get a complete array of instructions, tools, and templates for most challenges you'll face. In this practical and relevant guide, you'll learn how to: Identify problems with your content and persuade your bosses it's worth the time and resources to do it right Assemble a stellar team for your content project Prepare your organization for content transformation Make sense of your business environment and understand your audience Align stakeholders on business goals and user needs Set a compass for your content and decide how to measure success Create, maintain, and govern on-strategy content You'll learn how to treat content like the strategic asset that it is. "Quality content increases value. Poor-quality content destroys value. It's as simple as that. Meghan's book has specifi c, practical, and immediately actionable ideas that will help you increase the quality of your content." -GERRY MCGOVERN CEO, Customer Carewords "This second edition goes deep into three integral topics for content leaders- assembling cross-disciplinary teams, evaluating processes, and building a content playbook. If you're looking to build a new practice or retool an existing one, this book will help you succeed." -NATALIE MARIE DUNBAR Author, From Solo to Scaled: Building a Sustainable Content Strategy Practice.